Identificación, análisis y evaluación de los riesgos laborales del gobierno autónomo descentralizado municipal de Pangua (GADMUPAN). - Barriga Hidalgo, Carolina Estefanía (2018)
Nowadays, ocupational safety and health has become in an element of fundamental importance in organizations with their correct implementation and control; currently there are rules, decrees and international standars which are the guides that allow to choose the parameters to be met to preserve worker's integrity. In the last three years the municipality has presented a series of drawbacks with respect to occupational health and safety in their workers, being this the cause of accidents and above all, professionals diseases; the present investigation developed in the administrative and operational area of the Gobierno Autónomo Descentralizado Municipal de Pangua (GADMUPAN), it has as a main objective assess occupational risks and professional diseases of the workers in order to decrease or mitigate it; the method used for the proyect was the descriptive, that says,the information was acquired without change the environment and it's based on data collection through the matrix “INSHT”, that allowed a subsequent identification of the situation that the municipality presented. With the study done, it was observed through the evaluation with the technical guide “GTC 45”, that the most relevant risks are: physical, psychosocial, locative and ergonomic; while in the operative area the risks: mechanical, biological, chemical, electrical and locative are in a critical situation, as a result it can give reason to the descriptive method used at the beginning of the project, since with the simple fact of enter to the entity you can perceive the air of insecurity. When developing an improvement plan contributes with options to reduce the risks that were found, in this way you can weaken the possible risk factors that unfold in the middle, where develop the daily activities of the workers and therefore we also realized a risk map where the worker can observe what he is exposed in case of doesn’t wear personal protective equipment or take control measures for the present risks.